2022
DOI: 10.34123/icdsos.v2021i1.224
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Information and Communication Technology on The Welfare of Population in Eastern Indonesia

Abstract: During the Covid-19 pandemic, many countries in the world are expected to experience a slowdown or decrease in Human Development Index (HDI) growth including Indonesia. The disparities in development among regions to be one of the main issues in Indonesia. The gaps are not only occurring in HDI, but also in Information and Communication Technology (ICT) facilities between Western Indonesia and Eastern Indonesia. The purpose of this study is to analyze how Information and Communication Technology affects the We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
2
1
Order By: Relevance
“…Similarly, in long-term estimation, the probability for the ICT variable is 0.318, also exceeding the significance level of 0.05, signifying that ICT has no impact on HDI in the long run. This discovery is different from previous research conducted by (Al-Mursyid, 2019;Dewi et al, 2021;Saputra et al, 2022) who stated that the development of the ICT has a positive effect on HDI. These previous studies indicated that a higher level of information and communication technology correlates with an elevated quality of human development in each country.…”
Section: The Influence Of Ict On Hdi In Papua Provincecontrasting
confidence: 99%
See 2 more Smart Citations
“…Similarly, in long-term estimation, the probability for the ICT variable is 0.318, also exceeding the significance level of 0.05, signifying that ICT has no impact on HDI in the long run. This discovery is different from previous research conducted by (Al-Mursyid, 2019;Dewi et al, 2021;Saputra et al, 2022) who stated that the development of the ICT has a positive effect on HDI. These previous studies indicated that a higher level of information and communication technology correlates with an elevated quality of human development in each country.…”
Section: The Influence Of Ict On Hdi In Papua Provincecontrasting
confidence: 99%
“…In Indonesia, the government has initiated efforts to enhance education by instituting a mandatory 12-year education program. The implementation of this 12-year compulsory education program is anticipated to enhance the overall quality of education and consequently, improve the caliber of the human resources in the country, as mentioned in the study by Dewi et al (2021). However, it's noteworthy that in Papua Province, the average length of schooling stands at 6.76 years, which is roughly equivalent to completing elementary school education.…”
Section: The Influence Of Als On Hdi In Papua Provincementioning
confidence: 98%
See 1 more Smart Citation